PELATIHAN RESISTANCE EXERCISE THERABAND DAN TERAPI LATIHAN DALAM PENURUNAN NYERI BAHU DENGAN PEMBERIAN PADA LANSIA - Wahyono, Yulianto; pertiwi, jasmine kartiko (IFI cabang Kota Bekasi, 2024)
Changes in the musculoskeletal system in the elderly, such as decreased height, redistribution of muscle and fat mass, increased bone porosity, muscle atrophy, and joint stiffness, are part of the aging process. Musculoskeletal disorders such as shoulder pain or frozen shoulder are often found in the elderly. Frozen shoulder is a condition characterized by limited active and passive movement in the shoulder joint, often accompanied by pain and stiffness, which interferes with daily activities. This condition goes through four phases: pain, freezing, stiffness, and thawing, each lasting a certain period of time. Physiotherapy treatment usually focuses on pain management that occurs in each phase. Physiotherapists conducted resistance exercise theraband training and exercise therapy to reduce pain at the Tohudan posyandu which was attended by 35 elderly people. Theraband resistance exercise is isotonic exercise that uses a theraband, which is a very flexible colored rubber device. The exercise therapy given to the elderly is in the form of active movement, passive movement and hold relax. Evaluation was carried out using the SPADI index and the results showed that there was a reduction in shoulder pain.